Microbiological, physical, chemical and sensory characteristics of milk fermented with Lactobacillus plantarum - doi: 10.4025/actascihealthsci.v35i1.11939 - Aloisio Henrique Pereira de Souza; Giselle Aparecida Nobre Costa; Lúcia Helena da Silva Miglioranza; Luciana Furlaneto-Maia; Ana Flavia Oliveira (Universidade Estadual de Maringá, 2012)
This study developed a fermented milk with Lactobacillus plantarum and evaluated its microbiological, physical-chemical and sensory characteristics during 70 days of storage at 10ºC. The study analyzed the counts of total viable cells, total and thermotolerant coliforms, yeast and mold; acidity, pH, ash, fat and total solids; sensory evaluation and purchase intention of the final product by consumers. Nutrition information was compared with seven commercial brands of fermented dairy products. The final formula contained 10% sugar, 6% milk powder and 4% microbial inoculum. The final product was fat-free. Acidity, ash content and total solids were stable during storage, unlike pH. No total or thermotolerant coliforms, yeast or mold were detected. L. plantarum counts ranged from 10.1 Log10 CFU mL-1 at the beginning to 8.9 Log10 CFU mL-1 at the end of the storage period. The product had good acceptance and high purchase intent. The nutrition information of fermented milk was similar to those of commercial brands evaluated. L. plantarum demonstrated good viability in fermented milk, and although not considered a probiotic food in Brazil, it is promising for the production of foods with functional properties and/or health claims.